LipoxinA4 as a Potential Prognostic Marker of COVID-19. (5th July 2022) - Jamali, Farzaneh; Shahrami, Bita; Mojtahedzadeh, Amirmahdi; Najmeddin, Farhad; Arabzadeh, Amir Ahmad; Hadadi, Azar; Sharifzadeh, Mohammad; Mojtahedzadeh, Mojtaba
Abstract : This pilot study aimed to determine early changes of LXA4 levels among the hospitalized patients confirmed as COVID-19 cases following the clinical management and its correlation with commonly used inflammatory markers, including erythrocyte sedimentation rate (ESR), c-reactive protein (CRP), and ferritin. Thirty-one adult hospitalized patients infected with the non-severe COVID-19 were included. LXA4 levels were measured at the baseline and 48-72 hours after hospitalization. Accordingly, ESR and CRP levels were collected on the first day of hospitalization. Moreover, the maximum serum ferritin levels were determined during the five days. LXA4 levels significantly increased at 48-72 hours compared to the baseline. ESR, CRP, and ferritin levels were positively correlated with the increased LXA4. In contrast, aging was shown to negatively correlate with the increased LXA4 levels. LXA4 may be known as a valuable marker to assess the treatment response among non-elderly patients with non-severe COVID-19. Furthermore, LXA4 could be considered as a potential treatment option under inflammatory conditions. Further studies are necessary to clarify LXA4 role in COVID-19 pathogenesis, as well as the balance between such pro-resolving mediators and inflammatory parameters.